The relationship between employer branding, corporate reputation, and intention to apply - Junça Silva, A. (2022)
Employer branding is a topic that has gained relevance in the organisational world. Currently, organisations need to differentiate themselves and one of their biggest challenges is the search and retention of talent. One of the factors that have been associated with attracting talent is employer branding. However, studies that explore the relationship between this, corporate reputation, and the intention to apply for a job are scarce. As such, this study aimed to analyse the mediating role of corporate reputation in the relationship between employer branding and the intention to apply for a job offer. To achieve the goals, data were collected from 225 Portuguese adults. The response rate was 75%. Based on a survey, respondents reported their perceptions of employer branding of a specific organisation, they rated the organisation’s reputation and their intention to apply to that organisation. The results showed that employer branding (interest value; social value; economic value; development value; application value) positively influenced an organization's corporate reputation, which in turn increased an individual's intention to apply for an employment offer in that organisation. The present study is a contribution to the literature on employer branding, as it reinforced the importance that employer branding and corporate reputation play in the intention of applying for a job offer.